The ethical challenges of telemedicine in the field of oncology in South Africa - Pillay, Diana (My University, 2022)
Cancer is a complex condition requiring a multitude of interventions by various healthcare professionals within the healthcare continuum. Its growing incidence, particularly in developing countries, has resulted in widespread debate around a generally accepted definition of ethical cancer care. The situation is more complex in South Africa due to the inadequate healthcare resources and the longstanding cultural, linguistical, and socio-economic diversity amongst the population. In these circumstances, challenges arise in cancer treatment from the need to provide it in an ethical, equitable and acceptable manner. Telemedicine has been proposed by many health regulatory bodies as a means of improving healthcare delivery and access. For an action to have ethical value in the South African health arena, it needs to incorporate the notion of “philosophical good” by being recognisable as a something which is both right and acceptable. When seen through the lens of ethics, telemedicine in the South African would appear to hold great that promise. This report concentrates on one aspect of healthcare, namely oncology. This is a field which straddles a wide spectrum of care in which different levels can be defined. By consideration of the levels, an understanding can be developed to determine where telemedicine would possess ethical strengths and those where it has limitations. This evaluation of telemedicine in the broad field of oncology can present a viable argument for a hybrid model of cancer care in South Africa that would hold ethical value. However clear guidelines would need to be outlined to facilitate this amalgamation of care. The current telemedicine guidelines developed by the Health Professions Council of South Africa provide a generic framework on the ethical standard of practice expected by healthcare professionals. These guidelines however do not fully encompass the requirements expected of cancer treatment in general, nor are they entirely applicable to the particular circumstances arising from the different stages of the disease. To address this, while maintaining ethical integrity, the professional bodies affiliated to the field of oncology would need to expand on the current HPCSA guidelines and develop oncology specific telemedicine guidelines. This research report is a descriptive analysis of ethical principles and theories of telemedicine in the field of oncology. Using this ethical framework, I will propose situations where telemedicine can be advocated and where it would fail. Oncology specific telemedicine guidelines would advise healthcare professionals on the particular ethical considerations needed to support a hybrid model of cancer care to the South African patient. This would give telemedicine ethical justification and value. Conscious of the requirement to maintain ethical integrity, the conclusion to this thesis includes a proposal to this effect.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, 2022